2005
DOI: 10.1111/j.0742-2822.2005.03142.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Tricuspid Valve Morphology by Transthoracic Real‐Time‐3D‐Echocardiography

Abstract: 3D-TTE of the tricuspid valve can be performed in addition to routine 2D echocardiography within a reasonable time and with high assessability of important features in patients with right ventricular failure. Interrater agreement was fair to good overall. Thus, its feasibility may encourage prospective studies on its potential for more detailed noninvasive diagnosis and preoperative planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
3
22
2
Order By: Relevance
“…Schnabel et al have shown that transthoracic real-time 3D echo enabled better assessment of the whole tricuspid valve, with a satisfactory inter-rater agreement. 10 In the present study, the morphology of the whole tricuspid valve could not be depicted well on 2D echo. Although we attempted to trace the entire path of the PPM lead from various views, the relationship between the lead and the tricuspid apparatus remained unidentifiable.…”
Section: Discussioncontrasting
confidence: 71%
“…Schnabel et al have shown that transthoracic real-time 3D echo enabled better assessment of the whole tricuspid valve, with a satisfactory inter-rater agreement. 10 In the present study, the morphology of the whole tricuspid valve could not be depicted well on 2D echo. Although we attempted to trace the entire path of the PPM lead from various views, the relationship between the lead and the tricuspid apparatus remained unidentifiable.…”
Section: Discussioncontrasting
confidence: 71%
“…Schnabel et al also reported a high ability (96%) of 3-DE to assess the completeness of the tricuspid valve structure. 8 In the present study 2-DE showed poor assessment ability; Lin et al reported that PPM-induced tricuspid malfunction could be diagnosed preoperatively in only 5 of 41 patients (12%) who underwent surgery for PPM-related TR. 7 The present study confirmed the ability of 3-DE to identify PPM lead positions at the tricuspid valve.…”
Section: -Decontrasting
confidence: 58%
“…Schnabel et al also reported that image quality was less adequate in healthy subjects than in patients with RV dysfunction, 8 which may be related to the fact that the a dilated RV facilitates viewing of the tricuspid valve.…”
Section: -Dementioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental work has demonstrated that the current RT-3DE technique is also very promising for the assessment of intracardiac anatomy, not in the least because of its potential to present structural abnormalities in novel views (6)(7)(8)(9)(10)(11) . The intracardiac anatomy is especially interesting in structural heart disease, of which congenital heart disease is the main contributor.…”
Section: Introductionmentioning
confidence: 99%